2021
DOI: 10.1162/nol_a_00046
|View full text |Cite
|
Sign up to set email alerts
|

Moving From Bilingual Traits to States: Understanding Cognition and Language Processing Through Moment-to-Moment Variation

Abstract: The study of how bilingualism is linked to cognitive processing, including executive functioning, has historically focused on comparing bilinguals to monolinguals across a range of tasks. These group comparisons presume to capture relatively stable cognitive traits and have revealed important insights about the architecture of the language processing system that could not have been gleaned from studying monolinguals alone. However, there are drawbacks to using a groupcomparison, or Traits, approach. In this th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 145 publications
(183 reference statements)
0
15
0
Order By: Relevance
“…However, tasks recruit multiple control processes and may differ in their recruitment strength according to individual and task differences. Thus, it may be too simplistic to expect high between-tasks correlations (Salig et al, 2021). Another possibility is rooted in differences between linguistic and social contexts across studies, impacting transfer between cognitive systems (Barnett & Ceci, 2002; Sala et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, tasks recruit multiple control processes and may differ in their recruitment strength according to individual and task differences. Thus, it may be too simplistic to expect high between-tasks correlations (Salig et al, 2021). Another possibility is rooted in differences between linguistic and social contexts across studies, impacting transfer between cognitive systems (Barnett & Ceci, 2002; Sala et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The recent suggestion that a potential multilingual advantage lies in attentional systems [5,6] is accompanied by the recognition of the importance of considering individual differences in multilingual experiences [10,12]. It follows that a study of a varied range of individual multilingual experience factors in relation to attentional control can lead to important insights as to the nature of any multilingual cognitive advantage.…”
Section: The Current Studymentioning
confidence: 99%
“…Inconsistencies in findings could, for example, be explained by variability in study samples, where factors that vary between individuals are not taken into account. The current debate has therefore in turn sparked a reevaluation of the definition of multilingualism [9][10][11][12][ [9][10][11][12] and more research is conducted detailing the diversity of multilingual experiences and backgrounds (cf. [8] [8]).…”
Section: Introductionmentioning
confidence: 99%
“…While effects are not always replicated (see Lehtonen et al, 2018 ), studies have shown that, at least under certain conditions, the brain adapts structurally, functionally and chemically to bilingual experience (e.g., Stocco et al, 2014 ; Abutalebi and Green, 2016 ; Weekes et al, 2018 ; DeLuca et al, 2019a ; Pliatsikas, 2019 ; Grundy, 2020 ; Pliatsikas et al, 2021 ). And yet, the study of bilingualism and neurocognition has primarily focused on monolingual vs. bilingual (dichotomous) group comparisons across a variety of domains and tasks (see Salig et al, 2021 for review). While such an approach has led to keen insights into the bilingual mind and brain, it has also resulted in the nature of individual-level variables across bilinguals themselves to not be adequately addressed (Pliatsikas et al, 2020 ; Salig et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…And yet, the study of bilingualism and neurocognition has primarily focused on monolingual vs. bilingual (dichotomous) group comparisons across a variety of domains and tasks (see Salig et al, 2021 for review). While such an approach has led to keen insights into the bilingual mind and brain, it has also resulted in the nature of individual-level variables across bilinguals themselves to not be adequately addressed (Pliatsikas et al, 2020 ; Salig et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%